O lugar da poética na docência de projeto nos cursos de Arquitetura e Urbanismo: imaginário social e educação - Alberton, Josicler Orbem (2021)
The formation process of the architect and urban planner in professor, teaching professional, is the reason for this thesis which was developed by the Graduate Program in Education at the Federal University of Santa Maria (UFSM). The objective of the research was to investigate which are the poetic spaces of teaching in project in the Architecture and Urbanism courses based on the Social Imaginary (CASTORIADIS, 1982) and Philosophical Hermeneutics (GADAMER, 2015). For this, a dialogue was established with architects-teachers in order to produce narratives, verbal and visual, on subjects such as project teaching / learning, poetics and teaching. The methodology brought the image, in its active and mobilizing condition (BACHELARD, 2016 and 2008), and the ethical / aesthetic experience (HERMANN, 2010) to the center of the discussions on teacher education (FERRY, 1997). Based on the concept of game brought by Gadamer (2015), a method entitled -Game S.I.S.M.O - Imaginary Meanings in Motion - was designed specifically for the research of this thesis. The interpretations of the narratives corroborated the resumption of the cultural tradition of Architecture, pointing out the spatializations - constructed or represented in projects - as locus of the knowledge processes within the area. It was possible to identify those who derive from the University's democratization process as instituting imaginary. This context mobilizes complexities and contributes to the enhancement of the teaching profession, as it highlights the role of the architect-teacher as an active agent in social transformations. The reflections, based on the symbolic universe, start from the assumption that Architecture must be focused on the well-being of all and, in this perspective, all experiences matter for the construction of knowledge, science and for human formation. The results show that the poetic dimension can potentiate the process of formation of the architectteacher and that there is a diversity of poetic spaces in the teaching of design, inside and outside the Architecture and Urbanism Courses. However, the specificities of each area of knowledge and the importance of the role of educational institutions in teacher education processes must be considered because teaching, as well as the project in architecture, it is constituted in the collective. Finally, the method used to construct the narratives - the S.I.S.M.O Game - product generated by the thesis, mobilized the personal and professional dimensions, in discussions with the architect-teacher about teaching, and can be adapted to other training contexts.